A COMPREHENSIVE REVIEW OF THE APPLICATION OF AI AND IOT IN TRANSFORMING FINANCIAL MARKETS: EVIDENCE FROM SECONDARY DATA - Dr. Mukesh B. Ahirrao; Dr. Vishal S. Rana; Dr. Saroj B. Patil (International Engineering Journal For Research & Development, 2024)
The synergy between Artificial Intelligence (AI) and the Internet of Things (IoT) has reshaped finance. This research attempts to explore and understand their impact on finance, delving into AI's role in predictive analytics, customer interactions, and algorithmic trading, alongside IoT's integration into financial instruments for data generation and risk insights. The study employs a systematic review of academic journals, industry reports, and financial repositories, categorizing findings to analyze AI and IoT's influence on decision-making, risk management, and customer services. Key findings reveal AI's evolution to advanced machine learning, enhancing risk assessment and customer experiences. Concurrently, IoT devices transform data generation, aiding asset management and market predictions. Challenges like data privacy and biases in AI coexist with innovation opportunities in customer engagement and predictive analytics. Implications include transformative demands on financial institutions, improved decision-making for investors, and policy considerations for regulators addressing data security and biases in AI-driven systems. In conclusion, the fusion of AI and IoT drives a transformative shift in finance, offering innovation despite challenges. This research serves as a guide, highlighting implications and opportunities for a more efficient and inclusive financial industry